2013
DOI: 10.3762/bjoc.9.2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of spiro[dihydropyridine-oxindoles] via three-component reaction of arylamine, isatin and cyclopentane-1,3-dione

Abstract: SummaryA fast and convenient protocol for the synthesis of novel spiro[dihydropyridine-oxindole] derivatives in satisfactory yields was developed by the three-component reactions of arylamine, isatin and cyclopentane-1,3-dione in acetic acid at room temperature. On the other hand the condensation of isatin with two equivalents of cyclopentane-1,3-dione gave 3,3-bis(2-hydroxy-5-oxo-cyclopent-1-enyl)oxindole in high yields. The reaction mechanism and substrate scope of this novel reaction is briefly discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…187 In an exploratory experiment, the four-component reaction of p-methoxyaniline 110, dimethyl acetylenedicarboxylate 32, 1-benzyl-5-methylisatin 1 and cyclopentane-1,3-dione 259 in acetic acid was carried out by the same authors and there was no unit of acetylenedicarboxylate in the obtained product 260 (Scheme 103). 188 This result indicated that the three-component reaction of arylamine 110, isatin 1, and cyclopentane-1,3-dione 259 gave the final spiro[dihydropyridine-oxindole] compounds 260, while the acetylenedicarboxylate could not take part in the reaction.…”
Section: Scheme 101mentioning
confidence: 83%
“…187 In an exploratory experiment, the four-component reaction of p-methoxyaniline 110, dimethyl acetylenedicarboxylate 32, 1-benzyl-5-methylisatin 1 and cyclopentane-1,3-dione 259 in acetic acid was carried out by the same authors and there was no unit of acetylenedicarboxylate in the obtained product 260 (Scheme 103). 188 This result indicated that the three-component reaction of arylamine 110, isatin 1, and cyclopentane-1,3-dione 259 gave the final spiro[dihydropyridine-oxindole] compounds 260, while the acetylenedicarboxylate could not take part in the reaction.…”
Section: Scheme 101mentioning
confidence: 83%
“…From then on, many excellent synthetic protocols for the complex spiro‐oxindoles have emerged . We also successfully designed several three‐component or four‐component reactions containing Huisgen's 1,4‐dipoles to construct the versatile spiro‐oxindoles . In order to further demonstrate the potential applications of Huisgen's 1,4‐dipoles synthetic reactions, herein, we wish to report the three‐component reactions of isoquinoline with acetylenedicarboxylate and 3‐phenacylideneoxindoles for the synthesis of 2′,11b′‐dihydrospiro[indoline‐3,1′‐pyrido[2,1‐a]‐isoquinoline] derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, in recent years much attention has been paid to the diastereoselective and enantioselective synthesis of versatile spiro-oxirane-oxindoles [1419]. With the aim of expanding our previous studies on the synthesis of various spirooxindoles [2025], we decided to systematically investigate the Darzens reactions of a series of isatins with phenacyl bromides and report the facile synthesis of versatile spiro[indoline-3,2'-oxiran]-2-ones.…”
Section: Introductionmentioning
confidence: 99%